Integrated transcriptomic and metabolomic analysis reveals the molecular mechanisms underlying wheat germinating seed response to exogenous abscisic acid stress - Wang, Xiaolei; Chen, Chuchu; Sun, Xiaoxuan; Wang, Chuanzhi (Frontiers in Plant Physiology, 2025)
IntroductionPhytohormone abscisic acid (ABA) plays a pivotal regulatory role in crop responses to abiotic stress. However, the specificities of the coordinated transcriptional and metabolic regulatory network in wheat under ABA signaling remain to be fully elucidated.MethodsThis study systematically investigated the regulatory effects of exogenous ABA on wheat germinating seeds through integrated physiological, transcriptomic, and metabolomic analyses.ResultsPhysiological results demonstrated that low-concentration ABA (2 mg·L-1) promoted primary root elongation (12% increase vs. 0 mg·L-1 (CK)), whereas high concentrations (≥4 mg·L-1) significantly inhibited growth (40% root length reduction under 6 mg·L-1 ABA). Concurrently, electrolyte leakage, malondialdehyde (MDA) content, and catalase (CAT) activity markedly increased with ABA concentration (P < 0.05), indicating aggravated oxidative stress. Transcriptomic profiling (CK vs. 6 mg·L-1 ABA) identified 854 differentially expressed genes (DEGs; 470 up-regulated/384 down-regulated). Gene Ontology (GO) enrichment revealed DEGs predominantly involved in “Cellular process”, “Metabolic process”, “Catalytic activity”, and “Transporter activity”. KEGG analysis highlighted activation of “Linoleic acid metabolism”, “Alpha-Linolenic acid metabolism”, “Glycolysis/Gluconeogenesis”, and “Biosynthesis of amino acids” pathways. Metabolomics detected 665 differentially accumulated metabolites (DAMs), with “Lipids”, “Organic acids”, and “Amino acids” exhibiting significant alterations. KEGG enrichment emphasized “benzoxazinoid biosynthesis” and “Nicotinate/nicotinamide metabolism”. Integrative multi-omics analysis uncovered 10 core pathways, such as “Glycolysis/Gluconeogenesis”, “Biosynthesis of amino acids”, and “Cysteine and methionine metabolism”, that orchestrating ABA stress responses. Notably, L-serine and the genes TraesCS3A02G276100 and TraesCS5A02G398300 were recurrently implicated in multiple pathways, indicating their function as key network nodes.DiscussionThis study elucidates the molecular mechanisms by which wheat adapts to ABA stress through dynamic reprogramming of its metabolic and gene expression networks, thereby laying a theoretical foundation for developing future ABA-based seed treatment technologies or stress-resistant breeding strategies.